Chaos, CNN, memristors and beyond : a Festschrift for Leon Chua - Adamatzky, Andrew; Chen, G. (Guanrong); Chua, Leon O., 1936- (World Scientific Pub. Co., 2013)
This invaluable book is a unique collection of tributes to outstanding discoveries pioneered by Leon Chua in nonlinear circuits, cellular neural networks, and chaos. It is comprised of three parts. The first - cellular nonlinear networks, nonlinear circuits and cellular automata - deals with Chua's Lagrangian circuits, cellular wave computers, bio-inspired robotics and neuro-morphic architectures, toroidal chaos, synaptic cellular automata, history of Chua's circuits, cardiac arrhythmias, local activity principle, symmetry breaking and complexity, bifurcation trees, and Chua's views on nonline.